Ethnic, Gender, and Acculturation Influences on Sexual Behaviors - Meston, Cindy M.; Ahrold, Tierney (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2010)
Much research has been conducted on ethnic differences in sexuality, but few studies have systematically assessed the importance of acculturation in sexual behavior. The present study assessed general differences in normative sexual practices in healthy Euro-American, Asian, and Hispanic populations, using measures of acculturation to analyze the relative effects of heritage and mainstream cultures within each group. A total of 1,419 undergraduates (67% Euro-American, 17% Hispanic, 16% Asian; 33% men, 67% women) completed questionnaires which assessed sexual experience and causal sexual behaviors. In concordance with previous studies, Asians reported more conservative levels of sexual experience and frequency of sexual behaviors, fewer lifetime partners, and later ages of sexual debut than Euro-American or Hispanic counterparts. Hispanic reported sexual experiences similar to that of Euro-Americans. There was a significant interaction between mainstream and heritage acculturation in predicting number of lifetime sexual partners in Asian women such that the relationship between heritage acculturation and casual sexual behavior was stronger at lower levels of mainstream acculturation. On the other hand, in Hispanic men, higher levels of mainstream acculturation predicted more casual sexual behavior (one-time sexual encounters and number of lifetime sexual partners) when heritage acculturation was low but less casual sexual behavior when heritage acculturation was high. These results suggest that, for sexual behavior, Hispanic men follow an “ethnogenesis” model of acculturation while Asian women follow an “assimilation” model of acculturation.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexualité; thématiques; états-unis

Intersections: cultures, sexualités et genres - Brotman, Shari L.; Lévy, Joseph J. (Collection Santé et société, 2008)
Les intersections entre la culture, le genre et la sexualité retiennent aujourd’hui l’attention des chercheurs qui travaillent sur la diversité sexuelle, une tendance que l’on rencontre dans l’espace québécois et canadien. Plusieurs études ont ainsi porté sur ces enjeux parmi les autochtones et les groupes ethnoculturels. Cet ouvrage collectif, réalisé par des chercheurs, anglophones et francophones, de l’équipe pancanadienne Sexualités, Vulnérabilités et Résilience, présente ainsi un ensemble de travaux qui font le point sur ces questions. Les dimensions théoriques et méthodologiques sont ainsi cernées et des études empiriques, faisant appel à des approches quantitatives et qualitatives, traitent des trajectoires et des identités parmi différentes populations, des problèmes de santé auxquels elles peuvent être confrontées et des variations dans les usages sociosexuels d’Internet. Ce tour d’horizon aide à mieux comprendre la complexité des intersections touchant les identités sexuelles et les dimensions culturelles et suggère des pistes de recherche et d’intervention à développer.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; identités LGBTQIA2+; intersectionnalité; premier cycle; psychologie; périodes historiques; queer; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexologie; sexualité; thématiques; travail social